Job Satisfaction Analysis of Faculty Members in Public Sector Engineering Universities: An Empirical Investigation - Shahani, Ameer Ali; Tanwari, Anwaruddin; Marri, Hussain Bux; Korai, Mukhtiar Ali; Khan, Muhammad Ali (Mehran University Research Journal of Engineering and Technology; Vol 36 No 3 (2017): July Issue, 2017)
Most of the researchers have conducted study on the job satisfaction of the faculty members in Non– Engineering Universities only few have paid their attention in the Public Sector Engineering Universities. This study is the first attempt towards the research on faculty members’ job satisfaction in public sector engineering universities of Sindh, Pakistan. The focus of this research is to assess the faculty members’job satisfaction on the perspectives of different factors i.e. compensation, research and technology, management style, recognition, working environment, in-service teaching training. The data was collected and analyzed using SPSS version 17.0 on five point likert scale. Regression, Correlation and ANOVAs (Analysis of Variance) tests were conducted. Results showed that faculty members of the public sector engineering universities have lower job satisfaction. The finding suggested that, the study is useful for the management of universities in order to rectify the areas of dissatisfaction and to tackle the issues related to the faculty members regarding their job satisfaction.